2020
DOI: 10.1021/acssuschemeng.0c03905
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hydroprocessing, Fermentation, and Anaerobic Digestion in a Carbon-Negative Pyrolysis Refinery

Abstract: This study investigates the economic and environmental benefits of integrating hydroprocessing, fermentation, and anaerobic digestion into a pyrolysis refinery. Two scenarios were developed for upgrading and/or utilizing the primary products of pyrolysis (bio-oil, gas, and char). The first (hydroprocessing) scenario hydroprocesses whole bio-oil into gasoline and diesel. The second (fractionation) scenario fractionates bio-oil into sugars for fermentation to cellulosic ethanol and residual phenolic oil as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Techno-economic analysis at Iowa State University of fast pyrolysis biorefineries suggests a market price for biochar ranging between $50 and $100/metric ton. Urea price ranges between $377 and $407/metric ton or between $0.41 and $0.44/lb of N in the U.S. agricultural market. The prices of paraffin wax and Ca-LS vary between $600 and $1,000/metric ton and between $2,156 and $2,256/metric ton, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Techno-economic analysis at Iowa State University of fast pyrolysis biorefineries suggests a market price for biochar ranging between $50 and $100/metric ton. Urea price ranges between $377 and $407/metric ton or between $0.41 and $0.44/lb of N in the U.S. agricultural market. The prices of paraffin wax and Ca-LS vary between $600 and $1,000/metric ton and between $2,156 and $2,256/metric ton, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies at the Iowa State University have shown that biochar production is profitable as part of a fast pyrolysis biorefinery. Techno-economic analyses of fast pyrolysis biorefineries have estimated positive net present values while assuming a value for biochar of only $50–$100 per metric ton. While economic analyses have not yet been completed on the process to produce the ISIB biochar for slow-release fertilizer, autothermal pyrolysis simplifies the reactor design and reduces energy input requirements, thus reducing capital and operating expenses . Additionally, the method by which the biomass is pretreated has been evaluated using other pretreatments, most notably sulfuric acid.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, an LCA of biobased levoglucosan estimated its global warming potential to be half that of petroleum-derived chemicals 35 . TEA and LCA of an integrated pyrolysis and anaerobic digestion system for production of ethanol and phenolic compounds estimated the MFSP to be $1.21/gallon with net GHG emissions of -16.6 g CO 2e /MJ 13 .…”
Section: Introductionmentioning
confidence: 99%
“…35 TEA and LCA of an integrated pyrolysis and anaerobic digestion system for production of ethanol and phenolic compounds estimated the MFSP to be $1.21 per gallon with net GHG emissions of −16.6 g CO 2e per MJ. 13…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation